PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN OPEN ENDED PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL KELAS X SMA/MA - Sopiaten Sopiaten; Atma Murni; Syofni Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:This research is a development research that aims to produce learning tools, namely syllabus, lesson plans and student activity sheets (LAS) using the Problem Based Learning model with an open ended approach on the material of the Three Variable Linear Equation System for class X SMA/MA. This research is motivated by the importance of learning tools so that the arrangement is carried out as a form of planning from the steps of the learning process which are structured according to the objectives to be achieved. The development model used is the 4D model which consists of the stages of define, design, develop, and disseminate. The instruments used in this study were validation sheets and student response questionnaires. The learning tools that have been developed are validated by three validators and revised according to the validator's suggestions. The average validation score for the syllabus was 90.69%, RPP was 95.89%, and LAS was 93.23% with very valid categories. The results of this validation indicate that the syllabus, lesson plans, and LAS are feasible to be tested. The valid LAS was then tried out in small groups. The average result of the small group trial for LAS was 3.56 in the very practical category. Based on data analysis and discussion, it can be concluded that the syllabus, lesson plans and LAS developed using the Problem Based Learning model with the Open Ended approach in the material of the Three Variable Linear Equation System for class X SMA/MA have met the valid and practical criteria.Keywords : Learning Tools, Problem Based Learning Model, Open Ended Approach, ThreeVariable Linear Equation System, 4D Development Model.